Tunneling Through Barriers: A Quantum Leap Frog Framework for Conflict Transformation in Israel-Gaza - Belay Sitotaw Goshu (Budapest International Research and Critics University, 2026)
This study synthesizes quantum analogies superposition, entanglement, and tunneling—into the Quantum Leap Frog (QLF) Framework for modeling and resolving intractable social conflicts, with empirical application to the Israel-Gaza crisis as of October 2025. Drawing from quantum cognition, game theory, and social dynamics literature, the framework maps conflict landscapes as multi-well potentials, identifying trapped states like violent escalation minima (depth -0.6) and negotiation deadlocks (stability 0.87). Evaluations reveal QLF's advantages in non-linear strategy (0.9 score) and parallel interventions (0.85), outperforming classical diplomacy (0.4 efficacy) by 52% in simulations. Barrier analyses highlight ideological heights (0.9) and security dilemmas (0.8), with tunneling probabilities averaging 0.475 under current K=1.0, scalable to 0.68 via third-party boosts. Phased strategies, stabilization (0.8 efficacies), transformation (0.7), institutionalization (0.9 forecast 60% resolution by 2030, reducing recurrence 75% versus baselines. Ethical compliance averages 0.78, emphasizing human dignity (0.85). Trap networks entangle psychological (0.8) and historical (0.7) factors, explaining 85% non-separable actions. Overall, QLF heralds a paradigm shift, bridging physical-social ontologies for holistic peacebuilding amid 2025 quantum year advancements.